VOCABULARY LEARNING STRATEGIES OF SECONDARY SCHOOL STUDENTS - I. Gusti Astika (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
Strategy for learning vocabulary has an important role in English language acquisition. This study describes the vocabulary learning strategies that the students used when they learned new words. It attempted to find out if vocabulary learning strategies differed across school levels, gender, and ability groups as indicated by their English grades. This study involved 706 students from 8 secondary schools. The data were collected using a questionnaire developed using a taxonomy consisting of cognitive, metacognitive, memory, and determination categories. The overall results indicate that the students appear to rely more on determination strategies. This reliance on determination strategies is consistent across gender, ability groups, and school levels.